Obstacles and Opportunities for Preparing Competent Journalists at Universities in Bangladesh. (June 2016) - Ullah, Mohammad Sahid
This paper reports on a survey of the resources and capabilities, including infrastructure and logistics in 14 university-level Bangladeshi journalism institutions. Progress of the university journalism programmes is hampered by poorly resourced convergent news laboratory, shortage of research and teaching staff with professional media experience. It posits that university journalism programmes in Bangladesh, regardless of their ideological inclinations, should revamp their curriculum to emphasize on practical courses so as to keep pace with changing technologies in the newsroom.